Pengembangan Buku Cerita Bergambar untuk Meningkatkan Kemampuan Literasi Sains Peserta Didik Kelas 4 Sekolah Dasar - Rusydiana, Uzlifatul (Jurnal Didaktika Pendidikan Dasar, 2024)
Scientific literacy plays a crucial role for students in facing the problems of the 21st century. However, in fact, scientific literacy skills are still not optimal at SDN Prajuritkulon 2. This is because the learning process is more rote and the textbooks don’t contain scientific literacy skills. This research aims to produce a valid, practical and effective picture story book learning tool to improve the scientific literacy skills of grade 4 elementary school students. The research method used is R&D with static-group pretest-posttest design. The sample was grade 4 students with 30 students each as the control and experimental classes. Data collection uses validation sheets, observations, questionnaires and tests. Validation sheets, observations and questionnaires were analyzed using percentages. The results of the scientific literacy test were analyzed using N-Gain and the independent sample t test. The validation results show that the learning tool is very valid. The research results show that scientific literacy tests have increased. The independent sample t test obtained Sig. (2-tailed) 0.000 < 0.05. It can be concluded that the picture story book developed is valid, practical, effective, and can be used to train the scientific literacy skills of grade 4 elementary school students.